Bladder polyps in cloacal exstrophy: A histological series - John Jayman; Matthew Kasprenski; Mahir Maruf; Jonathan Epstein; Karl Benz; John P. Gearhart (Elsevier, 2018)
Prior literature has documented the histological characteristics and surgical outcomes of classic bladder exstrophy (CBE) patients with polyps, but there has been no documentation about the histology of cloacal exstrophy (CE) polyps. CE is a rare entity with an incidence of 1:400,000 live births and having a CE patient with polyps is an additional rarity [1,2]. With the scarcity of research on CE patients with polyps, the goal of this study is to describe the removal of CE polyps during bladder closure and to investigate polyp histology. Five patients were included in the current case series. They were treated at the authors' institution between 1999 and 2010. All had a successful initial bladder closure and had their polyps removed at the time of closure. The average age of primary bladder closure was 20.4 months. Only one patient had recurrent polyps following initial polyp removal, and the recurrent polyps were removed during a subsequent bladder stone procedure. The histologic characteristics of polyps in this series were heterogeneous. Keywords: Exstrophy, Cloacal, Bladder polyps